A new species of Janiralata Menzies, 1951 (Isopoda: Asellota, Janiridae) from Korea - Kim, Jeongho; Lee, Taekjun (Zootaxa, 2024)
A new isopod species, Janiralata kwangsooi sp. nov., from Dokdo Island located in the East Sea off the Korean Peninsula is described here. This species is distinguished from its congeners by the number of antennular articles, setation of mouthparts and pereopods, length and width ratio of appendages, and shape of male pleopods I and II. To aid species identification, a taxonomic key to species of Janiralata Menzies, 1951 in the Japanese and Korean waters is provided. A partial sequence of mitochondrial cytochrome-c-oxidase (COI) of this new species is also provided for DNA barcoding and compared with those of congeners publicly available in GenBank.